Materiality, Oral Incantations and Supernatural Agency in Ancient Healing Magic - Marco Simón, Francisco (Acta Classica Universitatis Scientiarum Debreceniensis, 2021)
In the Ancient World illness was thought to be the effect not of accidental or natural causes, but rather the result of a negative agency, an external attack on the victim’s body. This paper focuses on the diverse strategies used in healing magic attested in the material and textual records from the ancient Near East to Late Antiquity, with special attention paid to how the cultural status of objects and substances was changed through ritual, a process that, along with the invocations of demons and gods, allowed objects to acquire agency to counterattack the harm inflicted on the victim’s body.